SEASONAL VARIATION OF PARASITES OF FISHES IN LAKE CHARCHER WEST HARARGHE, OROMIA REGION, ETHIOPIA - GEBAWO, T. B (Nigerian Journal of Fisheries, 2014)
Samples of fishes collected from Lake Charcher by using gillnets of various mesh sizes were examined for parasitic infestation for three seasons named as rainy, post rainy and dry. A total of 431 samples were collected of which 383 were Oreochromis niloticus and 48 were Tilapia zilli. Total results showed 15.7% infection rate. The infection rate of parasites encountered were Clinostomum sp (3.9%), Contracaecum sp. (8.8%) and Eustrongylides (3%). The prevalence of parasite was high in post rainy season (29.2%) followed by rainy season (21.4%) and dry season (4.9%). Among the parasites recorded in the present study, the clinostomatid digeneans and Contracaecum nematodes could be medically important from public health point of view since the parasites can be transmitted to humans by eating raw fish. Therefore, further studies should be made for identification of other zoonotically important common fish parasites which might cause production loss in the fishery sector.